5x+60y=

Simple and best practice solution for 5x+60y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+60y= equation:


Simplifying
5x + 60y = 0

Solving
5x + 60y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-60y' to each side of the equation.
5x + 60y + -60y = 0 + -60y

Combine like terms: 60y + -60y = 0
5x + 0 = 0 + -60y
5x = 0 + -60y
Remove the zero:
5x = -60y

Divide each side by '5'.
x = -12y

Simplifying
x = -12y

See similar equations:

| -x+-11=-63 | | 72x^3-228x^2+140x= | | 88=-8(n-3) | | 2s+3s-14.4=6.8 | | 22(4x)=30 | | 8(w-8)=7(7+w) | | y^2-8y-10=0 | | x+(x+3)+(x-5)=78 | | 18(-2)-(-6)+5= | | 3x^3-7x^2+x= | | w^2-5w+4= | | 9=6-5d | | -2y-3+8=8-5y-12 | | 24x^4+18x^3-27x^2= | | (3n+22)+(2n+18)=180 | | -5(3-7a)=-85 | | 100-80+-4= | | 13a+1=17a+5 | | 15-5x=6-2x | | 6p-5p+5=-8-2(p+12) | | 10-3x-6-3x=7 | | 6-8(5+5p)=-194 | | 13+6p-9-4p-p=49 | | 65+18p=209 | | 15(x+3)=27 | | X^2-21x-110= | | -9+3(7-4w)= | | 6(-6r+8)+4=124 | | 7(-3x)= | | 9z-8-18z-28=27 | | 6(5-7)= | | t^2-8+10=0 |

Equations solver categories